Mastering AutoCAD 2012 and AutoCAD LT 2012 - Omura, George; Graham, Rick.; ebrary, Inc. (San Francisco, Calif. : Wiley Pub., 2011)
"Learn to master the AutoCAD softwareThis Autodesk Official Training guide is a comprehensive reference and tutorial that will help you quickly master AutoCAD software. Featuring concise explanations, step-by-step instructions, and hands-on projects based on real-world designs, this Autodesk Official Training Guide covers everything from interface best practices to hatches, fields, dynamic blocks, attributes, linking drawings to databases, rendering realistic views, and presenting designs. This Mastering book is recommended as a Certification Preparation study guide resource for the AutoCAD Associate and Professional exams. Serves as an in-depth resource on the fundamentals, functions, and features of AutoCAD, the popular 2D and 3D drawing software, and its less expensive version AutoCAD LT Describes how to effectively use hatches, fields, and tables; execute 3D modeling, imaging, and customizing; work with dynamic blocks, drawing curves, and solid fills; and more Features a DVD with more than a dozen video tutorials, "before and after" tutorial files, a trial version of AutoCAD, and additional tools and utilities Shares helpful examples, step-by-step instructions, and hands-on projects from award-winning author and CAD specialist George Omura This detailed tutorial is mandatory reading if you're eager to become proficient with AutoCAD or AutoCAD LT"--
Machine generated contents note: Part 1: The Basics.1 Exploring the AutoCAD and AutoCAD LT Interface.2 Creating Your First Drawing.3 Setting Up and Using AutoCAD's Drafting Tools.4 Organizing Objects with Blocks and Groups.5 Keeping Track of Layers and Blocks.Part 2: Mastering Intermediate Skills.6 Editing and Reusing Data to Work Efficiently.7 Mastering Viewing Tools, Hatches, and External References.8 Introducing Printing, Plotting, and Layouts.9 Understanding Plot Styles.10 Adding Text to Drawings.11 Using Fields and Tables.12 Using Dimensions.Part 3: Mastering Advanced Skills.13 Using Attributes.14 Copying Existing Drawings into AutoCAD.15 Advanced Editing and Organizing.16 Laying Out Your Printer Output.17 Making "Smart" Drawings with Parametric Tools.18 Using Dynamic Blocks.19 Drawing Curves.20 Getting and Exchanging Data from Drawings.Part 4: 3D Modeling and Imaging.21 Creating 3D Drawings.22 Using Advanced 3D Features.23 Rendering 3D Drawings.24 Editing and Visualizing 3D Solids.25 Exploring 3D Mesh Modeling.Part 5: Customization and Integration.26 Customizing Toolbars, Menus, Linetypes, and Hatch Patterns.27 Managing and Sharing Your Drawings.
Includes index.
Electronic reproduction.
Keywords: AutoCAD; Computer-aided design; Electronic books